الأسرة والعنف لدى فئة ذوى الاحتياجات الخاصة - عمار, رواب (Sciences humaines; Vol. 29 (2013): SCIENCES HUMAINES)
إن الأسرة إحدى العوامل الأساسية في بناء الكيان التربوي وإيجاد عملية التطبيع الاجتماعي، وإكسابه العادات التي تبقى ملازمة له طول حياته، فهي البذرة الأولى في تكوين النمو الفردي وبناء الشخصية، فإن الطفل في أغلب أحواله مقلّد لأبويه في عاداتهم وسلوكهم فهي أوضح قصداً، وأدق تنظيماً، وأكثر إحكاماً من سائر العوامل التربوية. ولذلك فإن التنشئة العامة للأطفال وتعليمهم القيم الأساسية للمجتمع تعتمد اعتمادا كليا على الأسرة وخاصة في المرحلة الأولى من حياة الطفولة فما بالك إذا كان هذا الأخير مصاب بإعاقة.        The family is one of the key factors in building entity, educational and a process of normalization, social, and improves their habits that remain inherent in all his life, it is the first seed in the composition of per capita growth and character building, the child in most of the conditions of an imitator of his parents in their habits and behavior are explained intentional, and less structured, And more compact than other educational factors. Therefore, the upbringing of the children and teach them the fundamental values of society depend entirely on the family and particularly in the first phase of the life of childhood, let alone if the latter with a disability.